THE STUDENTS’ PERCEPTION ON THE IMPLEMENTATION OF ENGLISH DAYS ACTIVITY AT ENGLISH STUDY PROGRAM ISLAMIC UNIVERSITY OF INDRAGIRI - Nani Agustina; Samsul Amri; Agus Mustajib (J-Shelves of Indragiri (JSI), 2022)
The importance of conducting this research is to introduce to students how English Day activities can help them get used to speaking English. Researchers conducted this research to find out information about students' perceptions of English talent on campus (English Study Program Islamic University of Indragiri) as an illustration of whether the implementation of English Days activities can support students' English language skills. The design of this research is descriptive-quantitative. This study's population consists of all students enrolled in the English Study Program, which is divided into three levels and four classes, namely, Semester 2 class A, Semester 2 class B, Semester 4 and Semester 6. To determine the sample, the researcher used the total sampling technique. The total population is 56 students. In collecting data, researchers used a questionnaire as a research tool. This questionnaire is being used to determine how students feel about the implementation of English Day activities at the Islamic University of Indragiri. The questionnaire used in the study had five (five) alternatives, known as the Likert scale. The results showed that students' perceptions of the implementation of English Day activities were good (75.3%), which were between 66 and 100 percent. So, it can be said that the students' perception of the implementation of English-day activities at the English Study Program Islamic University of Indragiri is good.